Improved Passive Synchronization for Complex Dynamical Networks with Randomly Occurring Distributed Coupling Time-Varying Delays via State Feedback Control (Contemporary Mathematics, 2025)
The improved synchronization of complex dynamical networks under passivity performance is the main topic of this paper. To distinguish between simple and complex dynamics in real-world scenarios, the effect of randomly occurring time-varying delays is specifically considered. The study is based on the development of a feedback controller and a Lyapunov-Krasovskii functional (LKF) with novel integral terms. Finally, a useful example is provided to illustrate the effectiveness of the proposed approach.
Keywords: complex networks; Chen-Lee systems, Lorenz-Stenflo systems, Liu-Chen systems, Active control, Synchronization; randomly occurring coupling delays; passivity; linear matrix inequality